The Efficiency of Monetary Policy Instruments on Inflation in Zambia Between 1990–2024 - Mwansa, Mukuka; Bednář, Milan, 1991-; Dungl, Daniel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This study evaluates the efficiency of Zambia’s monetary policy instruments in controlling inflation between 1990 and 2024, employing descriptive statistics and a Structural Vector Autoregression (SVAR) model. The descriptive analysis reveals that while money supply and inflation were highly volatile, the policy rate and real effective exchange rate remained relatively stable, suggesting a weak transmission of monetary policy to inflation outcomes. The SVAR results confirm a two-way relationship between money supply and inflation, with liquidity shocks spilling over into the broader economy and sustaining price pressures. In the long run, economic growth was influenced more by external shocks, political developments, and exchange rate fluctuations than by monetary interventions. Overall, the findings indicate that Zambia’s monetary policy has been only partially efficient, underscoring the need for stronger transmission channels, enhanced liquidity management, and broader structural reforms.
Vedoucí práce: Milan Bednář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses